A longitudinal analysis of impacts of court-mandated education finance reform on school district efficiency. Issue 1 (1st March 2014) - Eom, Tae Ho; Lee, Sock-Hwan
Abstract : While there has been increasing interest in the impact of courtmandated education finance reform on school district efficiency, research on the subject is scant. Taking advantage of New Jersey Supreme Court cases that have altered the way in which state school aid is distributed, this paper examines the effect of changes in the education finance system on school district efficiency. Building on existing literature on public sector efficiency, a longitudinal data analysis based on two-stage DEA models reveals that courtmandated increases in state aid to a limited number of poor school districts decreased the districts' efficiency. Though these results should be interpreted with some caution, in particular, the limitation of DEA as an efficiency measure, they imply that, as with any policy, policy makers and courts should be aware of how policy changes affect local government behavior and that it is necessary to evaluate policy outcome taking into account both resources and performance.